Effects of Thermal Diffusion and Radiation on Unsteady MHD Free Convection Flow Past an Infinite Heated Vertical Plate in a Porous Medium. (28th November 2012) - Sivaiah, S.; Anitha, K.; Venkataramana, S.
Abstract : We have explored the influence of thermal diffusion and radiation on unsteady magnetohydrodynamic free convection flow past an infinite heated vertical plate in a porous medium. The governing boundary layer equations are written into a dimensionless form by similarity transformations. The transformed nonlinear differential equations are solved numerically with finite element methods. Numerical calculations are carried out for different values of dimensionless parameters. The results are presented graphically for velocity, temperature, and concentration profiles and show that the flow field and other quantities of physical interest are significantly influenced by these parameters.